Pangangabit phenomenon from the perspective of the legal wife - Labaclado, Jessa A.; Ojeda, Nova Thirsty N (Jessa A. Labaclado, 2009)
This study investigated the pangangabit phenomenon from the perspective of the legal wife. First it sought to identify the condition of marriage prior to the pangangabit of the husband. Second, it explored the reasons why the husband engaged in pangangabit. And finally, it investigated the motivation of the husband to stay or remain in the extramarital affair. Following a descriptive-qualitative research design, the researchers interviewed ten legal wives with erring husbands in San Miguel, Leyte selected through purposive sampling. Furthermore, the co-triangulation method was utilized to avoid biases in the data by verifying their statements through their children.